Improved flowsheet of wastewater treatment from nitrogen-containing compounds - Semenova, O.; Reshetniak, L.; Bublienko, N.; Salavor, O.; Smirnova, E. (Problems of Environmental Biotechnology, 2015)
Wastewater containing nitrogen compounds stimulates the development of plankton, algae, and disrupts oxygen regime, which negatively affect the livelihoods of aquatic organisms. Sewage treatment from nitrogen compounds is carried out by active suspended sludge or immobilized active biomass.